Beta-cell function is associated with carotid intima-media thickness independently of insulin resistance in healthy individuals. Issue 4 (April 2016) - Roussel, Ronan; Natali, Andrea; Balkau, Beverley; Højlund, Kurt; Sánchez, Gabriel; Nolan, John J.; Mari, Andrea; Kozakova, Michaela; Bonnet, Fabrice
Abstract : Objective: It is a common belief that early atherosclerosis in prediabetes is causally linked to endothelial insulin resistance. Another condition, a low insulin secretion, may be associated with insufficient insulin action on the vascular wall and consequently favor atherosclerosis. Our aim was to test this hypothesis in people without diabetes, taking into account the gold-standard measurement of insulin sensitivity, a major confounder in the relationship between insulin secretion and atherosclerosis. Methods: We studied the European Relationship between Insulin Sensitivity and Cardiovascular Risk cohort of 451 men and 593 women (44 ± 8 years, mean ± SD) who were free of diabetes, hypertension, dyslipidemia, and other known chronic or acute conditions. All underwent an oral glucose tolerance test, a euglycemic-hyperinsulinemic clamp (M/I measured insulin sensitivity), and B-mode carotid ultrasound. Results: Intima–media thickness (IMT) in the common carotid artery was negatively associated with insulin secretion indexes, with Spearman partial correlation coefficients: –0.09, –0.08, –0.06 for respectively, the disposition index, the early insulin response and the beta cell glucose sensitivity, after adjusting for established factors, including clamp-measured insulin sensitivity (all P < 0.05). For quartiles 1 (lowest) to 4 of the disposition index, the covariate-adjusted geometric means of IMT (mm) were 0.605 (95% confidence interval: 0.596–0.614), 0.596 (0.587–0.605), 0.597 (0.587–0.606), and 0.586 (0.577–0.596) ( P trend = 0.004). Similar results were found for the two other surrogate measures of insulin secretion. No interaction with sex was observed. Conclusion: Insulin secretion was associated with early carotid atherosclerosis in nondiabetic individuals, independently of other risk factors, including insulin sensitivity measured by the gold-standard method.